Corrigendum to "Cervical penetration rates and efficiency of non-surgical embryo recovery in estrous-synchronized Santa Inês ewes after administration of estradiol ester (benzoate or cypionate) in combination with d-cloprostenol and oxytocin" [Anim. Reprod. Sci. 203 (2019) 25-32] - Fonseca, J. F.; Zambrini, F. N.; Guimarães, J. D.; Silva, M. R.; Oliveira, M. E.F. [UNESP]; Bartlewski, P. M.; Souza-Fabjan, J. M.G. (Elsevier, 2021)
The authors regret that the correct animal care protocol is incorrect and should be corrected to “15/2014” instead of “2,512.100,516”>. The authors would like to apologise for any inconvenience caused.
Corrigendum to “Cervical penetration rates and efficiency of non-surgical embryo recovery in estrous-synchronized Santa Inês ewes after administration of estradiol ester (benzoate or cypionate) in combination with d-cloprostenol and oxytocin” [Anim. Reprod. Sci. 203 (2019) 25–32] (Animal Reproduction Science (2019) 203 (25–32), (S0378432018310881), (10.1016/j.anireprosci.2019.02.004))